EFEKTIVITAS PELATIHAN PROGRAM KELOMPOK â€œAJIâ€ PADA GURU BIMBINGAN DAN KONSELING - Afiatin, Tina; Subandi, -; Haryanto, - (Faculty of Psychology, Universitas Gadjah Mada, 2000)
AJI (Adventurous Juvenile Intervention) is a training program designed for increasing group counseling skill in a natural setting by using â€œlearning by doingâ€ and â€œexperiential learningâ€ principle. Through this program school counselors not only have an opportunity to participate in-group counseling session but also practic to become a group counselor. This research aimed to test the effectiveness of AJI program in increasing the skill of school counselor for group counseling. The subject was 21 school counselors of middle school (SLTP) from Sleman Yogyakarta (11 male and 10 female; 12 subject hold S1 and 9 subject got D3 Diploma Degree). Quasiexperiment method was applied. The results indicate that there is a significant difference in the subjectâ€™s skill in counseling before and after intervention (t = -15.617; p < 0,01). There is also significant difference in the knowledge of group counseling (t = -20.414; p< 0,01). The qualitative data can be concluded that the school counselors get a deeper understanding of group counseling and its procedure as well as their ability to lead a group counseling for students. Overall, both quantitative and qualitative data analysis indicated that AJI program is effective in increasing the counseling skill of school counselors. Keyword: Adventurous Juvenile Intervention.